Simulasi Penggunaan Metode Proportional Integral Derivative Controller Neural Network Sebagai Kendali Kecepatan Motor Induksi 3 Fasa Berbasis Sensorless Field Oriented Control - Linda Sartika; Nur Faizah; Abdul Muis Prasetia (Jurnal Pendidikan Teknik Elektro Undiksha, 2025)
In designing this final project, the desired goal is to regulate the speed of a three-phase induction motor when the conditions are no-load or load-bearing using the Neural Network-PID controller method. The training data used is obtained from the pid, then the data is used as input and the target for the Neural Networkmethod. The pid-nn method works well based on the PID-NN transient response, the results of the pid-nn steady state response are 1499 rpm rise time 0.1480 s settling time 0,2008 s steady state error 0.06%, while for the PID and NN responses the same where the steady state response is 1497 rpm rise time 0.1479 s settling time 0.2134 s steady state error 0.2%, and for the PID- NN which was given a positive load resulted in a steady state error response of 2.53% which was better than the PID-NN experiments as evidenced by the steady state error response of 5.2%. The simulation results show that the PID-NN control gives good results.